2019
DOI: 10.14710/nmjn.v9i2.24821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Warning Score (EWS) Tutorial Simulation on Nurses' Knowledge and Clinical Performance

Abstract: Background: The Early Warning Score (EWS) system has been recommended for early identification tool of deterioration. However, its implementation has not been optimal; one of which is due to the low level of knowledge and understanding of EWS among nurses.Purpose: This study aimed to determine the effects of EWS tutorial simulation on nurses’ knowledge and clinical performance.Methods: This study employed a pretest posttest quasi-experimental design with a control group. Purposive sampling was used to recruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
1
6
0
13
Order By: Relevance
“…A similar finding was seen in other studies [12,20] The present study findings showed a highly significant statistical difference between total preknowledge and total post-knowledge score among the studied nurses' sample. This finding is supported by Damayanti, Trisyani, & Nuraeni [21] study. It revealed a significant difference in the pre-test and post-test knowledge within groups, both in the intervention and control groups.…”
Section: Discussionsupporting
confidence: 81%
“…A similar finding was seen in other studies [12,20] The present study findings showed a highly significant statistical difference between total preknowledge and total post-knowledge score among the studied nurses' sample. This finding is supported by Damayanti, Trisyani, & Nuraeni [21] study. It revealed a significant difference in the pre-test and post-test knowledge within groups, both in the intervention and control groups.…”
Section: Discussionsupporting
confidence: 81%
“…Kemampuan abstrak didapat dengan pelatihan tutorial, sementara kemampuan konkrit didapat dengan pelatihan simulasi. 9 Menurut Ozeckin LR et al, program pendidikan berbasis simulasi merupakan salah satu implementasi keperawatan untuk meningkatkan keselamatan pasien. 20 Dari hasil penelitiannya, didapatkan bahwa metode ini mampu meningkatkan pengenalan dan perawatan pasien dalam kondisi perburukan.…”
Section: Pembahasanunclassified
“…Hasil penelitian ini sama dengan penelitian oleh Damayanti R et al, dimana didapatkan skor delta pre-test dan posttest performa klinis antar kelompok sebesar 20 (kelompok intervensi) dan 12 (kelompok kontrol) secara bermakna. 9 Keberhasilan suatu pelatihan dipengaruhi oleh berbagai faktor diantaranya tersedianya modul pelatihan, materi pelatihan yang menarik, metode pelatihan, karakteristik situasional, karakteristik fasilitator dalam pelaksanaan pelatihan, karakteristik subjek pelatihan seperti kondisi awal peserta pelatihan serta kesungguhan peserta dalam mengikuti pelatihan partisipasi aktif peserta dalam mengikuti pelatihan. 22 Hal ini didukung penelitian oleh Andriana SF bahwa metode pelatihan merupakan salah satu faktor yang melatarbelakangi keberhasilan suatu pelatihan disamping latar belakang pendidikan formal terakhir, kemampuan instruktur dan dukungan sarana dan prasarana.…”
Section: Pembahasanunclassified
“…American Deteksi dini serta intervensi yang diberikan secara tepat akan berpengaruh terhadap peningkatan keamanan dan efektifnya perawatan yang diberikan untuk pasien dengan kondisi yang memburuk (Damayanti, Trisyani, Nuraeni. 2019).…”
Section: Kata Kunci: Early Warning Score System Henti Jantung Pengeta...unclassified